PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG PADA PT BINA SAN PRIMA SEMARANG - SITI AL MUTMAINAH, 14.01.65.0013 (Information Technology and Telematics, 2017)
Abstract - PT Bina San Prima is a company engaged in the distribution of drugs, food and drinks. PT Bina San Prima is currently using desktop-based system, making it less efficient because it can only be accessed in an office environment. Causing employees who are out of the office like a salesman having trouble locating customer data, knowing the inventory up to date. This will affect the provision of inaccurate information causes the customer to order goods are often out of stock or not even met. So sales of goods to be not optimal. Manager often to the field have difficulty in making the decision to demand for goods because they could not access the reports sales of goods, stock goods.  System development method used in this research waterfall with the beginning stages of the system, system analysis, system design with UML, system implementation by using PHP and MySQL.  The research result is a system inventory information PT Bina San Prima makes it easy to obtain a web-based inventory information and reports quickly. Keywords :information system, inventory, php, mysql